Technical project for drilling an exploration well in the Diam Niadio field (Senegal) - Moustapha, Mbengue (НТУ "Дніпровська політехніка", 2022)
The purpose of the work is to design a well at the Diam Niadio field (Senegal).
The thesis is compiled in accordance with the requirements of the guidelines. Contains information about the area of drilling, geological structure and characteristics of productive horizons. In the design part, the issues of well construction are resolved: the well structure has been designed, the equipment for the drilling rig, the rock cutting tool, the drilling and cementing technology have been selected. Measures have been developed to improve the quality of drilling fluids during preparation. Safety precautions are given when drilling wells. The issues of subsoil and environmental protection are highlighted. The estimate of well drilling has been substantiated
Keywords: PRODUCTION WELL, SKEW WALL, COMPLICATION, DRILLING FLUID PREPARATION.